2021
DOI: 10.3389/fnins.2021.607905
|View full text |Cite
|
Sign up to set email alerts
|

Surface Electromyography and Electroencephalogram-Based Gait Phase Recognition and Correlations Between Cortical and Locomotor Muscle in the Seven Gait Phases

Abstract: The classification of gait phases based on surface electromyography (sEMG) and electroencephalogram (EEG) can be used to the control systems of lower limb exoskeletons for the rehabilitation of patients with lower limb disorders. In this study, the slope sign change (SSC) and mean power frequency (MPF) features of EEG and sEMG were used to recognize the seven gait phases [loading response (LR), mid-stance (MST), terminal stance (TST), pre-swing (PSW), initial swing (ISW), mid-swing (MSW), and terminal swing (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Additionally, three studies independently found distinct patterns related to walking speed. They discovered that walking slowly resulted in higher NMC compared to walking at a faster pace (Chen et al, 2021; Petersen et al, 2012; Wei et al, 2021). Meanwhile, Chen et al reported that walking forward exhibited higher NMC when contrasted with walking backward (Chen et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, three studies independently found distinct patterns related to walking speed. They discovered that walking slowly resulted in higher NMC compared to walking at a faster pace (Chen et al, 2021; Petersen et al, 2012; Wei et al, 2021). Meanwhile, Chen et al reported that walking forward exhibited higher NMC when contrasted with walking backward (Chen et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, slow walking showed higher NMC compared to fast walking (Chen et al, 2021;Wei et al, 2021). During slow walking, there is a conscious adjustment of step length, balance, and control of limb movements needed to ensure stability.…”
Section: 4mentioning
confidence: 94%
“…Gait recognition is a technique that evaluates an individual's health status and rehabilitation level by analyzing their walking patterns [1][2][3] . In the medical and rehabilitation fields, gait recognition is of great significance for evaluating the rehabilitation process of patients with neurological diseases, musculoskeletal diseases, and neurological injuries [4][5][6] . In addition, gait recognition can also be applied in fields such as robot navigation, animation production, and movie special effects [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%